Poor access to health services for depression treatment in Brazil - Bezerra, Héllyda de Souza; Barbosa, Isabelle Ribeiro (Revista de Saúde Pública, 2023)
OBJECTIVE: To analyze the factors associated with poor access to health services for the depression treatment in Brazil. METHODS: This study used data from the Brazilian National Survey of Health, conducted in the years 2019 and 2020. The sample consisted of 8,332 individuals with a self-reported diagnosis of depression, and poor access to healthcare was identified from the question “what is the main reason for you to not visit the physician/health service regularly for your depression?” From which poor access was identified by the affirmative answer reporting distance of health services or difficulties with transportation; waiting time at the health service; financial difficulties; opening hours of the health service; Not being able to schedule a consultation via health insurance; does not know who to look for or where to go, among others. Sociodemographic aspects and health conditions were analyzed. Bivariate and multivariate analysis was performed using Poisson Regression. RESULTS: The prevalence of poor access to health services for depression treatment was 14.9% (95%CI: 13.6–16.2), relating to individuals aged 15–29 years (PR = 1.52) and 30-59 years old (PR = 1.22), without education (PR = 1.43), who rate their health as regular/poor/very poor (PR = 1.26), who have some limitation in their usual activities (PR = 2.71), who had the last consultation within 6 months of less than 2 years (PR = 2.63) and for more than 2 years (PR = 2.25) and who do not undergo psychotherapy (PR = 4.28). CONCLUSION: Poor access to health services for depression treatment was associated with individual factors and health conditions.